2019
DOI: 10.1016/j.vaccine.2018.12.026
|View full text |Cite
|
Sign up to set email alerts
|

An observer blinded, randomized, placebo-controlled, phase I dose escalation trial to evaluate the safety and immunogenicity of an inactivated West Nile virus Vaccine, HydroVax-001, in healthy adults

Abstract: Background West Nile virus (WNV) is the most common mosquito-borne infection in the United States. HydroVax-001 WNV is a hydrogen peroxide inactivated, whole virion (WNV-Kunjin strain) vaccine adjuvanted with aluminum hydroxide. Methods We performed a phase 1, randomized, placebo-controlled, double-blind (within dosing group), dose escalation clinical trial of the HydroVax-001 WNV vaccine administered via intramuscular injection. This trial evaluated 1 mcg and 4 mcg dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 35 publications
0
23
0
1
Order By: Relevance
“…Twenty individuals aged 18–49 received 1 µg of HydroVax-001 by the i.m. route and twenty received 4 µg [82]. The vaccine was given in two doses, four weeks apart.…”
Section: Phase I Clinical Trialsmentioning
confidence: 99%
“…Twenty individuals aged 18–49 received 1 µg of HydroVax-001 by the i.m. route and twenty received 4 µg [82]. The vaccine was given in two doses, four weeks apart.…”
Section: Phase I Clinical Trialsmentioning
confidence: 99%
“…These considerations motivated researchers to pursue the development of a new generation of classic inactivated flavivirus vaccines using Vero cell line as a substrate. 29,30 The new inactivated vaccine Evervac based on the strain Sofjin of the Far Eastern TBEV subtype was developed at the Chumakov Federal Scientific Center. Vero cell line obtained from the WHO reference cell bank was used as a substrate for the virus reproduction.…”
Section: Discussionmentioning
confidence: 99%
“…These considerations motivated researchers to pursue the development of a new generation of classic inactivated flavivirus vaccines using Vero cell line as a substrate. 29 , 30 …”
Section: Discussionmentioning
confidence: 99%
“…The authors indicate that this result might be improved by adding a third dose or by using an alternative inactivation protocol which combines hydrogen peroxide and formaldehyde. 20 Secondly, three doses of formaldehyde inactivated WNV particles induced high titers of neutralizing antibodies. 21 None of these WNV vaccine trials reported any adverse events or safety concerns which could impede further clinical testing.…”
Section: Wnv Vaccine Developmentmentioning
confidence: 99%